2022
DOI: 10.1021/acs.nanolett.2c00547
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Metal Anchored Zr6-Cluster-Porphyrin Framework Hollow Nanocapsules with Ultrahigh Active-Center Density for Electrocatalytic CO2 Reduction

Abstract: Designing earth-abundant electrocatalysts toward highly efficient CO 2 reduction has significant importance to decrease the global emission of greenhouse gas. Herein, we propose an efficient strategy to anchor non-noble metal single atoms on Zr 6 -cluster-porphyrin framework hollow nanocapsules with well-defined and abundant metal-N 4 porphyrin sites for efficient electrochemical CO 2 reduction. Among different transition metal single atoms (Mn, Fe, Co, Ni, and Cu), Co single-atom anchored Zr 6 -cluster-porphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Electrochemical conversion of greenhouse gas CO 2 into high-value added chemicals powered by renewable electricity under ambient conditions provides a promising route to achieving a carbon-neutral future and mitigating a global climate crisis. Previous literature reported that CO 2 can be reduced to various carbonous products (such as CO, , CH 4 , HCOOH, , ethylene, acetic acid, n-propanol, and so on) via electrochemical reaction paths. Among these products, HCOOH is broadly regarded as an ideal carrier molecule for hydrogen storage due to its easy access and high energy density. , However, the electrochemical CO 2 reduction reaction (CO 2 RR) is limited by high activation energy for the activation of thermodynamically stable CO 2 molecules and the competition of the hydrogen evolution reaction (HER) in aqueous solution. , Therefore, it is imperative to rationally design and construct advanced electrocatalysts with high activity and selectivity for the CO 2 RR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical conversion of greenhouse gas CO 2 into high-value added chemicals powered by renewable electricity under ambient conditions provides a promising route to achieving a carbon-neutral future and mitigating a global climate crisis. Previous literature reported that CO 2 can be reduced to various carbonous products (such as CO, , CH 4 , HCOOH, , ethylene, acetic acid, n-propanol, and so on) via electrochemical reaction paths. Among these products, HCOOH is broadly regarded as an ideal carrier molecule for hydrogen storage due to its easy access and high energy density. , However, the electrochemical CO 2 reduction reaction (CO 2 RR) is limited by high activation energy for the activation of thermodynamically stable CO 2 molecules and the competition of the hydrogen evolution reaction (HER) in aqueous solution. , Therefore, it is imperative to rationally design and construct advanced electrocatalysts with high activity and selectivity for the CO 2 RR.…”
mentioning
confidence: 99%
“…E lectrochemical conversion of greenhouse gas CO 2 into high-value added chemicals powered by renewable electricity under ambient conditions provides a promising route to achieving a carbon-neutral future and mitigating a global climate crisis. 1−4 Previous literature reported that CO 2 can be reduced to various carbonous products (such as CO, 5,6 CH 4 , 7 HCOOH, 8,9 ethylene, 10 acetic acid, 11 n-propanol, 12 and so on) via electrochemical reaction paths. Among these products, HCOOH is broadly regarded as an ideal carrier molecule for hydrogen storage due to its easy access and high energy density.…”
mentioning
confidence: 99%
“…2 The conversion of CO 2 into fuels is a highly promising approach to alleviate the environmental and energy crisis. 3 Compared with thermochemical, biochemical, and photocatalytic conversion, the electrochemical CO 2 RR has attracted more and more attention because of mild conditions, controllable reaction parameters, and the employment of renewable and off-peak electricity. 4,5 Intriguingly, the electrochemical CO 2 RR can produce C 2 H 4 , which is an important industrial chemical feedstock with a huge market demand and a high economic value.…”
mentioning
confidence: 99%
“…Single atom catalysts have attracted more attention in heterogeneous catalysis conversion reactions such as electrochemical CO 2 reduction, N 2 reduction, ,, O 2 reduction, and H 2 O decomposition reactions , because the maximum surface atomic utilization as well as the controllably tailored physical and chemical properties. Amal et al reported employing Cu single atom catalysts (SACs) for electrochemical urea synthesis (Figure a–i) .…”
Section: Discussionmentioning
confidence: 99%